Profile of typhoid fever in admitted pediatric patients from tertiary care hospital - Dr Pankti Desai; Dr Abidali Y Vijapura (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Typhoid fever is preventable infectious diseases caused by gram negative bacteria Salmonella typhi and is still a major public health problem in India. Objective: The main aim of our study was to find out the clinical profile in admitted pediatric patients of typhoid fever. Design: Retrospective case study .Subjects: 292 hospitalized Widal positive typhoid fever pediatric cases admitted to tertiary care hospital from1st August 2014 to 31st July 2015. Methods: Records of all the patients who were discharged with the diagnosis of Widal Positive enteric fever were retrieved, compiled and analyzed. Results: Out of 292 total patients: 18(6.16 %) were below 2 years of age; 54(18.49%) cases were between 2-5 years; 124(42.46%) were between 5 to 10 years of age and 96 (32.87%) were above 10 years of age. Fever was the main presenting complains in all cases. Vomiting (49.31%), diarrhea (36.98%) and cough (33.56) were common associated complains. Almost all (289, 98.97%) patients were treated with Injection ceftriaxone after positive Widal reports to start with. Only in 62(21.23%) patients, oral Azithromycin was added along with ceftriaxone. 58.20% patients required more than 6 days hospital stay. Conclusion: The incidence of typhoid fever was 5.63 % amongst the total admitted patients. Typhoid fever is having high morbidity but with availability of third generation cephalosporin, mortality has reduced. 24.65% patients were below 5 years of age which shows changing trends in age of presentation which was considered rare below 5 years of age.